2009
DOI: 10.1001/archneurol.2009.57
|View full text |Cite
|
Sign up to set email alerts
|

Diffusely Abnormal White Matter in Chronic Multiple Sclerosis

Abstract: Background: Diffuse abnormalities in the white matter (WM), ie, the so-called diffusely abnormal WM (DAWM), as observed on magnetic resonance imaging (MRI), may contribute to the development of clinical disability in multiple sclerosis (MS). Underlying pathologic and MRI characteristics of DAWM are largely unknown.Objectives: To explore and describe the histopathologic and radiologic characteristics of DAWM in chronic MS.Design: An MRI and histopathologic postmortem correlative study. Methods:We analyzed 17 fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

19
172
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 156 publications
(192 citation statements)
references
References 28 publications
19
172
1
Order By: Relevance
“…These findings mirror postmortem evidence showing that the lesion edge surrounding areas are characterized by a partial decrease in myelin density with an intermediate level between discrete lesions and NAWM,28, 29, 30, 31 and that the severity of myelin destruction inside lesions becomes progressively worse from the periphery to the center 28…”
Section: Discussionsupporting
confidence: 83%
“…These findings mirror postmortem evidence showing that the lesion edge surrounding areas are characterized by a partial decrease in myelin density with an intermediate level between discrete lesions and NAWM,28, 29, 30, 31 and that the severity of myelin destruction inside lesions becomes progressively worse from the periphery to the center 28…”
Section: Discussionsupporting
confidence: 83%
“…These abnormalities have been referred to as dirty WM, dirty-appearing WM, or DAWM. [1][2][3][4] The use of varying criteria renders comparisons among these studies difficult. A previous article has proposed a set of MR imaging criteria to define DAWM, applied them in a postmortem setting, and concluded that the use of these specific criteria yields only areas with truly diffuse pathology, without including multifocal lesional pathology.…”
mentioning
confidence: 99%
“…A previous article has proposed a set of MR imaging criteria to define DAWM, applied them in a postmortem setting, and concluded that the use of these specific criteria yields only areas with truly diffuse pathology, without including multifocal lesional pathology. 4 Recently, these areas of DAWM have been characterized histopathologically and were found to contain tissue changes indicating a chronic pathology, including axonal loss, myelin loss, and chronic isomorphic gliosis. 4,5 However, the severity of these changes may vary among patients.…”
mentioning
confidence: 99%
See 2 more Smart Citations